THE RISE OF SUSTAINABLE FINANCE: PAVING THE WAY FOR A GREENER FUTURE - Abdusadiqov Zohidjon Olimjon o’g’li (Лучшие интеллектуальные исследования, 2023)
Abstract: The global financial landscape has witnessed a remarkable transformation with the growing prominence of sustainable finance in recent years. This article provides an insightful exploration of the evolving landscape of sustainable finance, focusing on the integration of sustainable and responsible investing practices, the emergence of green banking initiatives, and the increasing adoption of Environmental, Social, and Governance (ESG) criteria in financial decision-making processes. Highlighting the imperative need for environmentally conscious and socially responsible investment practices, the article emphasizes the pivotal role of sustainable finance in fostering long-term sustainability and ethical responsibility. By analyzing the implications of sustainable finance on the financial sector and the broader global community, the article underscores the potential of sustainable finance to drive positive change and pave the way for a more environmentally conscious and socially responsible global economy.